Managing Carious Lesions: Consensus Recommendations on Terminology. (May 2016) - Innes, N.P.T.; Frencken, J.E.; Bjørndal, L.; Maltz, M.; Manton, D.J.; Ricketts, D.; Van Landuyt, K.; Banerjee, A.; Campus, G.; Doméjean, S.; Fontana, M.; Leal, S.; et al.
Variation in the terminology used to describe clinical management of carious lesions has contributed to a lack of clarity in the scientific literature and beyond. In this article, the International Caries Consensus Collaboration presents 1) issues around terminology, a scoping review of current words used in the literature for caries removal techniques, and 2) agreed terms and definitions, explaining how these were decided. Dental caries is the name of the disease, and the carious lesion is the consequence and manifestation of the disease—the signs or symptoms of the disease. The term dental caries management should be limited to situations involving control of the disease through preventive and noninvasive means at a patient level, whereas carious lesion management controls the disease symptoms at the tooth level. While it is not possible to directly relate the visual appearance of carious lesions' clinical manifestations to the histopathology, we have based the terminology around the clinical consequences of disease (soft, leathery, firm, and hard dentine). Approaches to carious tissue removal are defined: 1) selective removal of carious tissue —including selective removal to soft dentine and selective removal to firm dentine ; 2) stepwise removal —including stage 1, selective removal to soft dentine, and stage 2, selective removal to firm dentine 6 to 12 mo later; and 3) nonselective removal to hard dentine —formerly known as complete caries removal (technique no longer recommended). Adoption of these terms, around managing dental caries and its sequelae, will facilitate improved understanding and communication among researchers and within dental educators and the wider clinical dentistry community.